Bookcreator Bermuatan Kearifan Lokal sebagai Media Penguatan Literasi Baca Digital - Samsiyah, Nur (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Read literacy is not just reading but needs to be connected with technology and local wisdom to be in line with the demands of the times. The aim of this research is to describe strengthening digital literacy through bookcreators containing local wisdom in elementary schools. Data was collected through observation, questionnaire interviews and tests. Instrumens include interview sheets, observation sheets, questionnaires and description questions. The students who were the research subjects were 4th grade students at the Josenan 1 elementary school in Madiun City with a total of 25 students. The results of the research show that students are enthusiastic about telling stories about local wisdom, enjoy reading bookcreators and the test results for making concept maps of main ideas and supporting ideas received a score of 3.57 in terms of accuracy, neatness and time. Student activities in strengthening reading literacy need to be carried out every day to familiarize students with literacy. It is hoped that the local wisdom contained in the bookcreator can make students understand and appreciate the local culture around them